WACANA TOLERANSI ISLAM DALAM BERAGAMA PADA CHANNEL YOUTUBE JEDA NULIS EPISODE COKI BERTANYA HABIB MENJAWAB (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The subject matter of this research discusses the discourse of the text on Islamic tolerance in religion on the writing pause youtube channel. This subject matter has subproblems, namely: (1) How does the text discourse on the youtube channel pause writing the episode Coki asks Habib to answer, and (2) What is the dimension of social cognition and social context in the youtube channel. The results of this study are using discourse analysis, which consists of text analysis, social cognition, and social context. So that the message to be conveyed can be analyzed more clearly. This is because text analysis uses three parts, namely macrostructure, superstructure, and macrostructure. These three parts can be further divided into six parts, namely thematic, schematic, semantic, syntactic, stylistic, and rhetorical. The implication in this research is that it is hoped that the Pause Nulis account owner uses a scientific language style, it will also be an attraction for research activists, especially in the academic world related to tolerance, it is hoped that the technicality of the writing pause account in this case Audio on the YouTube channel Habib Jafar please update so that the noises from outside voices can be smoothed, it is hoped that the contents of the writing break can be more profound, which is closely related to tolerance in the review of the Al-Quran and Hadith, and we hope to invite guest speakers or guest stars who understand Islam so that the audience can learn more, not just watching popular people like Coki.